Improving the efficacy of proteasome inhibitors in the treatment of renal cell carcinoma by combination with the human immunodeficiency virus (HIV)-protease inhibitors lopinavir or nelfinavir - Abt, Dominik; Besse, Andrej; Sedlarikova, Lenka; Kraus, Marianne; Bader, Juergen; Silzle, Tobias; Vodinska, Martina; Slaby, Ondrej; Schmid, Hans-Peter; Engeler, Daniel Stephan; Driessen, Christoph; Besse, Lenka (BJU international, 2018)
OBJECTIVES: To assess the potential of second-generation proteasome inhibition by carfilzomib and its combination with the human immunodeficiency virus (HIV) protease inhibitors (HIV-PIs) lopinavir and nelfinavir in vitro for improved treatment of clear cell renal cell cancer (ccRCC). MATERIALS AND METHODS: Cytotoxicity, reactive oxygen species (ROS) production, and unfolded protein response (UPR) activation of proteasome inhibitors, HIV-PIs, and their combination were assessed in three cell lines and primary cells derived from three ccRCC tumours by MTS assay, flow cytometry, quantitative reverse transcriptase-polymerase chain reaction and western blot, respectively. Proteasome activity was determined by activity based probes. Flow cytometry was used to assess apoptosis by annexin V/propidium iodide assay and ATP-binding cassette sub-family B member 1 (ABCB1) activity by MitoTracker™ Green FM efflux assay (Thermo Fisher Scientific, MA, USA). RESULTS: Lopinavir and nelfinavir significantly increased the cytotoxic effect of carfilzomib in all cell lines and primary cells. ABCB1 efflux pump inhibition, induction of ROS production, and UPR pre-activation by lopinavir were identified as underlying mechanisms of this strong synergistic effect. Combined treatment led to unresolved protein stress, increased activation of pro-apoptotic UPR pathway, and a significant increase in apoptosis. CONCLUSION: The combination of the proteasome inhibitor carfilzomib and the HIV-PIs lopinavir and nelfinavir has a strong synergistic cytotoxic activity against ccRCCin vitro at therapeutically relevant drug concentrations. This effect is most likely explained by synergistic UPR triggering and ABCB1-modulation caused by HIV-PIs. Our findings suggest that combined treatment of second-generation proteasome inhibitors and HIV-PIs should be investigated in patients with metastatic RCC within a clinical trial.
Keywords: inhibitory HIV-proteasy; nádorové buněčné linie; Carcinoma, Renal Cell; nelfinavir; HIV Protease Inhibitors; lidé; Proteasome Inhibitors; carfilzomib; karcinom z renálních buněk; Cell Line, Tumor; renal cell cancer; Antineoplastic Agents; Kidney Neoplasms; stres endoplazmatického retikula; Lopinavir; chemorezistence; lopinavir; protinádorové látky; bortezomib; Humans; inhibitory proteasomu; Drug Resistance, Neoplasm; Endoplasmic Reticulum Stress; HIV-protease inhibitors; Nelfinavir; #KidneyCancer; proteasome inhibitors; nádory ledvin; #KCSM